The Effects of Extracorporeal Shock Wave Therapy on Spastic Muscle of the Wrist Joint in Stroke Survivors: Evidence From Neuromechanical Analysis - Leng, Yan; Lo, Wai Leung Ambrose; Hu, Chengpeng; Bian, Ruihao; Xu, Zhiqin; Shan, Xiyao; Huang, Dongfeng; Li, Le (Frontiers in Neuroscience, 2021)
Background: This study combined neuromechanical modeling analysis, muscle tone measurement from mechanical indentation and electrical impedance myography to assess the neural and peripheral contribution to spasticity post stroke at wrist joint. It also investigated the training effects and explored the underlying mechanism of radial extracorporeal shock wave (rESW) on spasticity. Methods: People with first occurrence of stroke were randomly allocated to rESW intervention or control group. The intervention group received one session of rESW therapy, followed by routine therapy which was the same frequency and intensity as the control group. Outcome measures were: 1) NeuroFlexor method measured neural component (NC), elastic component (EC) and viscosity component (VC) and 2) myotonometer measured muscle tone (F) and stiffness (S), 3) electrical impedance myography measured resistance (R), reactance (X) and phase angle (θ); 4) modified Asworth scale; 5) Fugl Meyer Upper limb scale. All outcome measures were recorded at baseline, immediately post rESW and at one-week follow-up. The differences between the paretic and non-paretic side were assessed by t-test. The effectiveness of rESW treatment were analyzed by repeated-measures one-way analysis of variance (ANOVA) at different time points. Results: Twenty-seven participants completed the study. NC, EC and VC of the Neuroflexor method, F and S from myotonometer were all significantly higher on the paretic side than those from the non-paretic side. R, X and θ from electrical impedance were significantly lower on the paretic side than the non-paretic side. Immediately after rESW intervention, VC, F and S were significantly reduced, and X was significantly increased. The clinical scores showed improvements immediate post rESW and at one-week follow-up. Conclusions: The observed changes in upper limb muscle properties adds further support to the theory that both the neural and peripheral components play a role in muscle spasticity. ESW intervention may be more effective in addressing the peripheral component of spasticity in terms of muscle mechanical properties changes. The clinical management of post stroke spasticity should take into consideration of both the neural and non-neural factors in order to identify optimal intervention regime.